Identification of two novel mutations, PSEN1 E280K and PRNP G127S, in a Malaysian family - Ch’ng GS (Dove Medical Press, 2015)
Gaik-Siew Ch’ng,1,* Seong Soo A An,2,* Sun Oh Bae,2 Eva Bagyinszky,2 SangYun Kim3,41Department of Genetics, Kuala Lumpur Hospital, Malaysia; 2Department of Bionano Technology, Gachon University, 3Department of Neurology, Seoul National University College of Medicine, 4Seoul National University Bundang Hospital, South Korea*These authors contributed equally to this workAbstract: Alzheimer’s disease (AD) is the most common form of dementia, which can be categorized into two main forms: early onset AD and late onset AD. The genetic background of early onset AD is well understood, and three genes, the APP, PSEN1, and PSEN2 have been identified as causative genes. In the current study, we tested three siblings from Malaysia who were diagnosed with early onset dementia, as well as their available family members. The family history was positive as their deceased father was similarly affected. Patients were tested for mutations in APP, PSEN1, PSEN2, and PRNP. A novel variant, E280K, was discovered in exon 8 of PSEN1 in the three siblings. In silico analyses with SIFT, SNAP, and PolyPhen2 prediction tools and three-dimensional modeling were performed, and the results suggested that the mutation is probably a pathogenic variant. Two additional pathogenic mutations were previously been described for codon 280, E280A, and E280G, which could support the importance of the E280 residue in the PS1 protein contributing to the pathogenic nature of E280K. Additional ten family members were screened for the E280K mutation, and all of them were negative. Six of them presented with a variety of neuropsychiatric symptoms, including learning disabilities, epilepsy, and schizophrenia, while four family members were asymptomatic. A novel PRNP G127S mutation was found in a step-niece of the three siblings harboring the PSEN1 E280K mutation. In silico predictions for PRNP G127S mutation suggested that this might be possibly a damaging variant. Additional studies to characterize PRNP G127S would be necessary to further understand the effects of this mutation. Keywords: Alzheimer’s disease, presenilin-1, prion, mutation